LINGUOCULTURAL SPECIFICITY OF EMOTION VERBALIZATION: A COMPARATIVE STUDY OF ENGLISH AND UZBEK IDIOMATIC EXPRESSIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the linguocultural specificity of emotion verbalization through a comparative analysis of English and Uzbek idiomatic expressions. Idioms serve as important linguistic tools for expressing emotions and reflect the cultural values, beliefs, and cognitive patterns of a speech community. The study explores similarities and differences in the representation of emotions such as happiness, sadness, anger, fear, and love in English and Uzbek idioms. The findings reveal that while some emotional concepts are universal, their linguistic realization is strongly influenced by cultural and historical factors. The research contributes to the fields of linguoculturology, cognitive linguistics, and cross-cultural communication.
Keywords: emotion verbalization, idiomatic expressions, linguocultural specificity, English language, Uzbek language, comparative linguistics, cultural semantics.